2017
DOI: 10.5751/es-09442-220328
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of French community gardens as environmental stewardships

Abstract: ABSTRACT. Community-based efforts are essential to address urban social-ecological challenges. Here, we focus on French community gardens. Through participant observation and semistructured interviews, this study seeks to provide empirical evidence on: (1) what motivates volunteer gardeners in French community gardens to undertake this activity, (2) what practices take place in the gardens, and (3) which individual and collective processes are associated with gardeners' experiences in the gardens. Through thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…During the visits to the gardens, it was found that some of them, located in public areas, no longer existed, with the area being used for the construction of squares and highways. Although research in different countries has shown that green spaces in residential areas can contribute to food security and the sustainability of urban systems [ 27 29 ] and the lack of government support, as well as the absence of public policies aimed at supply and urban agriculture, can contribute to the decline in municipal agricultural production [ 5 ], as also observed in the present study.…”
Section: Resultsmentioning
confidence: 53%
“…During the visits to the gardens, it was found that some of them, located in public areas, no longer existed, with the area being used for the construction of squares and highways. Although research in different countries has shown that green spaces in residential areas can contribute to food security and the sustainability of urban systems [ 27 29 ] and the lack of government support, as well as the absence of public policies aimed at supply and urban agriculture, can contribute to the decline in municipal agricultural production [ 5 ], as also observed in the present study.…”
Section: Resultsmentioning
confidence: 53%
“…In the international literature community gardens appear as multifunctional sites that can simultaneously fulfil goals related to food-provisioning, community building and environmental education (Firth et al 2011;Russ et al 2015;Torres et al 2017). In some contexts where the gardens explicitly challenge the current patterns of food production and the usage of public space, they can be interpreted as sites for collective action and local activism (Nettle 2014).…”
Section: Urban Community Gardening and Its Deliberative Potentialmentioning
confidence: 99%
“…These collective approaches qualified as ordinary environmentalism (Blanc and Paddeu 2018) are presented from an apolitical perspective based around frequently banal day-today environmental concerns and practices: air and water quality, urban sprawl, urban agriculture, protection of biodiversity, preservation of parks and forests, waste management and recycling, energy transition, food consumption patterns, etc. Born out of investments in the public space based on personal or collective needs (i.e., recreational, food, nature-related, social) (Torres et al 2017), the collectives primarily carry out local work to preserve, manage, monitor, advocate for rights, and/or educate on the local environment and quality of urban life Campbell 2008, Fisher et al 2012).…”
Section: Issues Tackledmentioning
confidence: 99%
“…Rather than just privatization of space, we may speak of the dynamics of the contribution of ordinary environmentalism to the socialecological quality of public spaces in the general interest. The term social-ecological system Gunderson 2012, Folke et al 2016) therefore appears appropriate for describing the ways in which these activist practices make a positive contribution to living habitats (Torres et al 2017). Much research has already focused on the possible instrumentation and instrumentalization of "stewardship" practices.…”
Section: Issues Tackledmentioning
confidence: 99%